Ponds’ Water Quality Analysis and Impact of Heavy Metals on Fishes’ Body - Ndayisenga, J.D.; Dusabe, S. (Journal of Sustainability and Environmental Management, 2022)
The anthropogenic activities have caused increase in the aquatic heavy metals pollution. The higher concentration of heavy metals in fish’s body also affects the consumers as it reaches to human body through the food chain. This study was conducted to analyze the ponds’ water quality based on physicochemical parameters and nutrients in relation to the dissolved heavy metals accumulated in the fishes’ body by using R programing. In this study, the heavy metals bio-accumulated from barrage pond and diversions ponds was analysed. Kigembe, Nyamagana, Rwasave fertilized and Rwasave non-fertilized ponds were purposively chosen for the study. The water sample was analysed using HACH DR5000 UV-Vis Spectrophotometer to measure Ammonium-Nitrogen, Nitrate-Nitrogen, Phosphates and Total Phosphorus at Chemistry Department’s Laboratory of University of Rwanda. While after filtration of water samples using Whatman filter papers, heavy metals including Fe, Cu, Mn, Zn, Ni, Co, Cd, Cr and Pb were determined using ICP-MS 7900. The analysis of physicochemical parameters showed that the temperature, pH, Conductivity, Turbidity and TDS were within the permissible limit of ponds’ water (20-300C, 6.5-9, less than 1000 µs/cm, 30-60 NTU and less than 2000 mg/L respectively) quality for all the sites except Rwasave fishponds, where lower pH was observed. The nutrients level in these ponds were low comparing to the standard limit. The assessed heavy metals were Fe, Cu, Mn, Zn, Cd, Cr and Pb whose concentrations analyzed in water were within permissible limit of 0.3ppm, 1ppm, 0.1ppm, 3ppm, 0.003ppm, 0.5ppm and 0.01ppm respectively while heavy metals bio-accumulated were within the permissible limit of 0.1ppm, 1ppm, 0.05ppm, 5ppm, 0.05ppm, 0.05ppm and 0.05ppm respectively for all the sites except for both dissolved and bio-accumulated Fe and Mn concentration which were high for all sites. The highest level of heavy metals concentration was obtained in particular Fe and Mn. This shows that there is urgent need of continuous water quality analysis within the ponds for maintaining the favorite conditions for fish. The water quality monitoring will help the farmers to create the safe aquatic environment for fishes and improve their production output.